Предмет: Алгебра,
автор: annazo2001
Решите уравнения срочно надо
Ответы
Автор ответа:
0
(3х+3)/х(х+2)-(2х-1)/(х-2)(х+2)=(3-х)/х(х-2)(х+2)
х≠0, х≠2, х≠-2
(3х+3)(х-2)-(2х-1)*х=3-х
3х²-6х+3х-6-2х²+х-3+х=0
х²-х-6=0
х1+х2=1 и х1*х2=-6⇒х1=3 и х2=-2-не удов усл
х≠0, х≠2, х≠-2
(3х+3)(х-2)-(2х-1)*х=3-х
3х²-6х+3х-6-2х²+х-3+х=0
х²-х-6=0
х1+х2=1 и х1*х2=-6⇒х1=3 и х2=-2-не удов усл
Похожие вопросы
Предмет: Математика,
автор: Аноним
Предмет: Биология,
автор: Alex150305
Предмет: Алгебра,
автор: webipa8353
Предмет: Алгебра,
автор: Nekit20130
Предмет: Алгебра,
автор: MaddyGimple